ACADEMIC SELF CONCEPT OF LITHUANIAN UNIVERSITIES TEACHERS– EXPRESSION OF COGNITIVE COMPONENT - Rastauskienė, Giedrė Judita; Kardelis, Kęstutis; Šeščilienė, Ina Marija (Acta Paedagogica Vilnensia, 2008)
Many Lithuanian and foreign authors investigate problems related to academic values of the university teacher. There are a lot of discussions about rendering of academic service for society (university included) and about significance and importance of scientific research for the university teacher. According to the data solving problems of higher education system seem to be complex and related to determinating psychosocial factors of university teacher activities.Deep alterations in Lithuanian political, economic and social life during period of independence impact on public attitudes towards education in the context of knowledge economics and determine qualitative new relationship between the university teacher and academe – academic self concept (particular completeness of perceived social features of academe member, emotions and assessments induced by these features).The aim of this article is to present research results on expression of cognitive component of Lithuanian universities’ teachers’ academic self concept linked to: 1. perception of himself as a builder of knowledge society, an educator or a member of social institution; 2. duration of his/her pedagogic and scientific career; 3. reliance on scienctific area.Representative sample was formed by 454 teachers from 8 Lithuanian universities. Considering the new context of teacher’s education the respondents were grouped according to the duration of their career – teachers who started their pedagogic and scientific career in the universities before 1991 and teachers who started their pedagogic and scientific career after 1991.Attitudes of respondents towards affirmations of categories of cognitive component of academic self concept were analysed and interpreted by using standardization of data and non-parametric statistics. The analysis of categories of cognitive component of academic self concept of teachers indicated that the expression of this component pertains to duration of teacher’s pedagogic and scientific career (the same as teacher’s age) and reliance on scientific area.
Keywords: higher education; academic identity; academic self-concept